Kajian Pengendalian Malaria di Provinsi Sumatera Utara dalam Upaya Mencapai Eliminasi Malaria - Lukman Hakim; Upik Kesumawati Hadi; Sugiarto Sugiarto (Jurnal Vektor Penyakit, 2018)
Abstract North Sumatera province was the largest contributor to malaria positive cases for Sumatera island in 2016. This study aim was to analyze the malaria situation in North Sumatera, subsequently taken into consideration for the preparation of a strategic plan to achieve the elimination of malaria in the region. Malaria case data, figures on Slide Positivity Rate, Annual Parasite Incidence, and plasmodium species were derived fromthe entire districts and cities of the North Sumatera province. Data were collected from 2010 - 2016. The data were analyzed qualitatively or descriptively. The results showed the Annual Parasite Incidence in North Sumatera had tended to decline from 0.91 per 1000 population in 2010 to 0.27 per 1000 population in 2016. The results showed the number of Slide Positivity Rate increased from 8.80 % in 2010 to 17.06 % in 2013 but decreased to 8.71 % in 2016. Target elimination of malaria in North Sumatera (2020) can be achieved when the discovery of cases of malaria, such as the enhanced efforts in intensification and extension, followed by improvement of malaria case management and vector control. Abstrak Provinsi Sumatera Utara termasuk daerah malaria penyumbang terbanyak kasus positif malaria di Pulau Sumatera pada tahun 2016. Penelitian ini bertujuan untuk menganalisis situasi malaria di Provinsi Sumatera Utara, selanjutnya menjadi bahan pertimbangan untuk penyusunan rencana strategis dalam tercapainya eliminasi malaria di wilayah ini. Data kasus malaria, angka Slide Positivity Rate, angka Annual Parasite Incidence, jenis Plasmodium dan lainnya diperoleh dari seluruh kabupaten/kota di Provinsi Sumatera Utara. Data dikumpulkan dari tahun 2010-2016. Analisis data dilakukan secara kualitatif atau descriptive analysis. Hasil penelitian menunjukkan saat ini angka Annual Parasite Incidence malaria di Provinsi SumateraUtara sudah cenderung menurun dari 0,91 per 1000 penduduk pada tahun 2010 menjadi 0,27 per 1000 penduduk pada tahun 2016. Namun, angka Slide Positivity Rate dari pada tahun 2010 mempunyai kecenderungan meningkat dari 8,80 % pada tahun 2010 meningkat terus sampai 17,06% pada tahun 2013, walaupun menurun lagi menjadi 8,71 % pada tahun 2016. Target eliminasi malaria di Sumatera Utara tahun 2020 dapat dicapai apabila penemuan kasus malaria, seperti upaya intensifikasi dan ekstensifikasi ditingkatkan, diikuti dengan perbaikan penatalaksanaan kasus, dan pengendalian vektor.